2022
DOI: 10.5194/gmd-15-6197-2022
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid ensemble-variational data assimilation in ABC-DA within a tropical framework

Abstract: Abstract. Hybrid ensemble-variational data assimilation (DA) methods have gained significant traction in recent years. These methods aim to alleviate the limitations and maximise the advantages offered by ensemble or variational methods. Most existing hybrid applications focus on the mid-latitudinal context; almost none have explored its benefits in the tropical context. In this article, hybrid ensemble-variational DA is introduced to a tropical configuration of a simplified non-hydrostatic convective-scale fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Environmental administration (Viranda et al, 2020). Management of projects (Kusuma and Bima, 2022), software development (Lee et al, 2022), and so on. Demdoum et al (2021) investigated the usage of the ABC accounting system and its applicability in the environmental accounting approach, which is geared toward the green economy, namely in the areas of digital Strategy, governance, and organizational restructuring.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Environmental administration (Viranda et al, 2020). Management of projects (Kusuma and Bima, 2022), software development (Lee et al, 2022), and so on. Demdoum et al (2021) investigated the usage of the ABC accounting system and its applicability in the environmental accounting approach, which is geared toward the green economy, namely in the areas of digital Strategy, governance, and organizational restructuring.…”
Section: Literature Reviewmentioning
confidence: 99%
“…environmental management (Viranda et al, 2020). Project management (Kusuma and Bima, 2022), software development (Lee et al, 2022), etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…That study found that these balances, in the mid-latitude cases, are an advantage when analysing the larger scales but are a disadvantage at small scales. The model has also been used in a tropical setting, where the DA method has been expanded to include a hybrid (ensemble-variational) capability (Lee et al, 2022). Until now however, the ABC model has lacked a water variable, meaning that studies have been limited to dry dynamics only, where the model shows little evidence of sporadic convective behaviour.…”
Section: Introductionmentioning
confidence: 99%